2001
DOI: 10.1046/j.1365-201x.2001.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel modified Ussing chamber for the study of absorption and secretion in human endoscopic biopsies

Abstract: The aim of this study was to design and evaluate a modified Ussing chamber, that makes use of constant air suction (modified Ussing air suction chamber, MUAS) for fixation of biopsy specimens. Standard size forceps biopsies were taken from the descending part of duodenum from patients undergoing endoscopy. Short circuit current (SCC) and conductance (G) were measured during basal conditions and after addition of different sugars and secretagogues. Histologic examination was performed to determine the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 28 publications
2
67
2
Order By: Relevance
“…Obese subjects probably are less sensitive to CCK and GLP-1, and therefore need higher circulating levels to reach a similar satiety effect. and Isc refl ects the ionic fl uxes across the epithelium [35][36][37]. In the present study, basal electrical parameters varied over a wide range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese subjects probably are less sensitive to CCK and GLP-1, and therefore need higher circulating levels to reach a similar satiety effect. and Isc refl ects the ionic fl uxes across the epithelium [35][36][37]. In the present study, basal electrical parameters varied over a wide range.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the only known sweet sensing receptor is the heterodimeric receptor T1R2/T1R3 which displays an intriguingly broad sensitivity for naturally occurring sweet substances such as glucose, fructose, sucrose, and sweet-tasting D-amino acids, but also for synthetic sweeteners like aspartame (NutraSweet®), sucralose (Splenda®), cyclamate, saccharin, and acesulfame K [35,36]. T1R2/T1R3 is expressed both in taste buds of the oral cavity [36], and throughout the GI tract [37][38][39].…”
Section: Carbohydrate Sensing Receptorsmentioning
confidence: 99%
“…In previous studies of human intestinal mucosa maintained in Ussing chambers, I sc and G t were stable for at least 2 h and the epithelial surface remained histologically intact for at least 2.5 h (Larsen et al, 2001;Soderholm et al, 1998). Because epithelial degradation and edema occur after several hours of incubation (Figure 2 and (Larsen et al, 2001;Soderholm et al, 1998), experiments in the Ussing chamber were limited to 2 to 3 h. Glucose-stimulated Na + absorption at the end of the incubation period demonstrated that the JPP was functionally intact (Larsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Use of 10 times magnification through a stereomicroscope (Nikon, Tokyo) ensured correct mucosa-serosa orientation and appropriate fixation. Biopsies were fixed by constant air suction [17] . The exposed tissue area varied from 3.4 to 5 mm 2 , depending on the used insert, which was chosen to match the tissue size.…”
Section: Mounting Of Biopsies and Electrical Measurementsmentioning
confidence: 99%
“…We hypothesized that disturbances in the duodenal secretory reflex arches involving 5-HT play a pathogenic role in FD. Measurement of ion transport in human epithelia in vivo requires invasive methods; however a modified Ussing chamber for human endoscopic biopsies has been developed in our laboratory [17] . In the present study, 5-HT induced ion transport is measured in FD patients and healthy controls.…”
Section: Introductionmentioning
confidence: 99%